Outpatient management of acute uncomplicated diverticulitis results in health-care cost savings. (3rd April 2018) - Isacson, Daniel; Andreasson, Karl; Nikberg, Maziar; Smedh, Kenneth; Chabok, Abbas
Abstract: Purpose: Outpatient management without antibiotics has been shown to be safe for selected patients diagnosed with acute uncomplicated diverticulitis (AUD). The aim of this study was to evaluate the impact on admissions, complication rates and health-care costs of the policy of outpatient treatment without using antibiotics. Methods: The medical records of all patients diagnosed with AUD in the year before (2011) and after (2014) the implementation of outpatient management without antibiotics in Västmanland County were reviewed. Health-care cost analysis was performed using the Swedish cost-per-patient model. Results: In total, 494 episodes of AUD were identified, 254 in 2011 and 240 in 2014. The proportion of patients managed as outpatients was 20% in 2011 compared with 60% in 2014 ( p  < .001). There were 203 hospital admissions and a total length of stay of 677 days in 2011 compared with 95 admissions and 344 days in 2014 (both p  < .001). The total health-care cost was €558, 679 in 2011 compared with €370, 370 in 2014 ( p  < .001). Three patients developed complications in 2011 and four in 2014 ( p  = .469). Conclusions: The new policy of outpatient management without antibiotics in routine health care almost halved the total health-care cost without an increase in the complication rate.